Fatores de risco para depressão pós-parto - Ramos, Kelly Campara Machado (2020)
The birth of a child marks important changes in maternal life, usually accompanied by deep emotions ranging from pleasure to despair. Several studies document the negative reactions by mothers, and Postpartum Depression has special attention because it is the most common morbidity in mothers within a period of up to one year after delivery and can reach up to one in seven mothers. Thus, the present study aims to elucidate the prevalence of postpartum depression, and the factors associated to this pathology and its respective statistical significance. This study was conducted at the University Hospital, in Santa Maria, Brazil. It is a cross-sectional, quantitative study, carried out from the completion of an epidemiological questionnaire and application of the Edinburgh Postnatal Depression Scale (EPDS) aiming to screen puerperal women with symptoms compatible with puerperal depression who had their delivery at the Santa Maria University Hospital and underwent consultation at the puerperal outpatient clinic from June to October 2019. Scores greater than or equal to ten. They were considered positive and sent for evaluation by a specialized professional. The data were statistically evaluated by the SPSS 18.0 program. A total of 171 puerperal women were analyzed, and 29.8% of the mothers presented a score compatible with puerperal depression. It was verified with statistical significance that not having postpartum depression is closely associated with uneven breastfeeding (p=0.002 and χ=12.533). On the contrary, not having a planned pregnancy (p=0.0175 χ2=5.717), having had depression at any stage of life (p=0.013 χ2=6.237), depression during pregnancy (p≤0.0001 χ2=46.201) or having a history of depression in the family (p=0.001 χ2=10.527), are factors related to the development of postpartum depression. But only having depression during pregnancy was found to be an important risk factor for the occurrence of postpartum depression, increasing by 12 times (OR: 12.891) the risk of developing this pathology. Therefore, depression during pregnancy is an important risk factor for the development of postpartum depression and can easily, through the Edinburgh Postpartum Depression Scale, be diagnosed and treated in a timely manner.